A inspeção do trabalho no governo FHC: uma análise sobre a política de fiscalização do trabalho. - Miguel, Antonia Celene (Universidade Federal de São Carlos, 2004)
Through the analysis of the politics of fiscalization of the in the period fhc, we show that the labor inspection is an important actor for the agreement of the labor market as a normative space. The actions of the labor inspection display the labourite guide lines delineated and decided accordant the labourite politics applied by the labor ministry each government.
Keywords: Ciência política; Políticas públicas; Trabalho - inspeção; Mercado de trabalho; Political science; Public politics; Labor inspection; Labor market; CIENCIAS HUMANAS::CIENCIA POLITICA